Self-Care Education Influences Self-Concept in Patients with the Chronicle of Kidney Disease - Andy Putra Ndruru; Erma Lingga; Hari Sandi Bahagia Siregar; Chrismis Novalinda Ginting (Global Health Science Group, 2020)
Chronicle of kidney disease is caused kidney ca not or able to carry out his job. Is a sense of the self-concept, trust, and the individual knew about him and affecting individuals in connection. The self-concept covering the body image, self-esteem, ideal self, identity, and the role of self. The purpose of the study was to analyze the effect of self care education on self-concept of patients with chronic kidney failure. Descriptive analytic research through one group design pre and post test in which the variables of self care education and its influence on the self-concept variables of patients with chronic kidney failure were studied simultaneously. This study uses primary data collection techniques, with a population of 150 and a sample of 34 patients. Analysis of this data using bivariate analysis using statistical tests Wilcoxon Signed Rank Test at the significance level (α) 0.05. The results showed that self care education influenced the self-concept in patients with chronic renal failure with a value of sig (2tailed) = 0,000 (α = 0.05). This study concludes that self care education has a significant effect on the self-concept of patients with chronic kidney failure in Royal Prima Hospital Medan.